Cultural Diversity and Worship: The Role of Ethnic Music in Eliezer Sentani Congregation - Sahureka, Cosye Meilina; Parinussa, Nelinio (Universitas Negeri Surabaya, 2023)
Caring for the congregation through the presence of ethnic music in weekly worship and religious festivals brings a new atmosphere to the Eliezer congregation in Sentani. The purpose of this study is to provide an overview of the forms, impacts, and meanings of ethnic music in the Eliezer Sentani congregation. The ethnic music and singing are a collaboration of six different ethnic groups: Papua, Maluku, NTT, Sulawesi (Toraja-Minahasa), Java, and North Sumatra (Batak). The method used is a qualitative descriptive method that employs data triangulation through document analysis, observation, and two types of interviews: focused interviews and free interviews. Data is analyzed by combining these three data sources and then providing a description and conclusions about the observed phenomenon. The results of this research reveal that the worship with ethnic nuances in GPI Eliezer Sentani can be seen in terms of its form, meaning, and impact. The form of worship with ethnic elements involves traditional music components in various combinations, serving the purpose of adding aesthetics and color to worship and devotion. In terms of meaning, the use of ethnic music in worship acts as a means of promoting culture and as a tool for unity and togetherness. Regarding its impact, the use of ethnic music in worship has led to an improvement in the quality and quantity of congregation members participating in the worship.